2015
DOI: 10.1111/liv.12808
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of transient elastography in assessing liver fibrosis in chronic viral hepatitis: A multicentre, retrospective study

Abstract: TE can accurately assess the degree of liver fibrosis in Korean patients with CVH. TE was superior to APRI for predicting each fibrosis stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 45 publications
7
61
0
Order By: Relevance
“…However, histological assessment was not selected as an independent predictor of HCC and LRE development when adjusted with and without LS value. In contrast, it was demonstrated that TE could assess the fibrotic burden with acceptable accuracy (AUC more than 0.8 for each fibrosis stage) similar to a vast amount of previous studies, 13,19,25 and that TE was independently prognostic in predicting HCC and LRE development even after adjusting for LB and other variables. These findings support the necessity to check LS values at the time of starting antiviral therapy.…”
Section: Discussionsupporting
confidence: 69%
“…However, histological assessment was not selected as an independent predictor of HCC and LRE development when adjusted with and without LS value. In contrast, it was demonstrated that TE could assess the fibrotic burden with acceptable accuracy (AUC more than 0.8 for each fibrosis stage) similar to a vast amount of previous studies, 13,19,25 and that TE was independently prognostic in predicting HCC and LRE development even after adjusting for LB and other variables. These findings support the necessity to check LS values at the time of starting antiviral therapy.…”
Section: Discussionsupporting
confidence: 69%
“…20,22,23,3134 In our cross-sectional analysis, LS value showed accuracy similar to that encountered in prior studies (AUC: 0.823–0.848), 23,35 suggesting that even with the limited size of this cohort, patient characteristics were appropriate for evaluating WFA + -M2BP as well. However, the diagnostic accuracy of WFA + -M2BP (AUC ∼0.7) proved unsatisfactory, compared with other studies (AUC >0.8).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, longitudinal analysis of LS indicated only borderline statistical significance in assessing the risk of developing HCC ( P  = .065), despite notable similarity to previous TE-based investigations (AUC >0.8). 23,35 Given that LS value is a known factor in predicting the risk of HCC, 21,31,32 this seemingly inconsistent outcome may be related to the limited sampling. Sample size was also inadequate to systematically control relevant variables, such as antiviral agent use, existing cirrhosis, and necroinflammatory activity, for subgroup analyses, even though the appropriate adjustments were made in multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a liver biopsy only samples approximately 1/50000 of the liver, there have been concerns with sampling errors despite an adequate number of portal tracts and sample size[7,10,11]. Intra- and inter-observer variation in histological interpretation has also been reported[12,13]. Given these limitations, much research has been dedicated to evaluating non-invasive methods to determine liver fibrosis[5,9].…”
Section: Introductionmentioning
confidence: 99%